Normative Legal Regulation of Teaching the Ukrainian Language in Secondary School in the 1960s-1970s of ХХ century - Svitlana Kutova (Pedagogical Discourse, 2013)
The analysis of educational normative legal documents of the 1960s-1970s has been done in the article. The attention is drawn to the role of the law «On Strengthening of Connection of School with Life» in the development of public education and teaching the Ukrainian language in particular. The dynamics of conducting reorganizational measures in the system of schooling of Ukrainian SSR has been traced. The influence of politics of the government of that time onto the educational process at schools has been reflected. Objective complications of teaching the Ukrainian language, stipulated by the number of reformatory actions, which were conducted by the Ministry of Education of Ukrainian SSR, Council of Ministers and Central Committee of Communist Party of Ukraine have been cleared up.